1980
DOI: 10.1016/s0022-5347(17)55271-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of Bladder Carcinoma

Abstract: Urine cytology is a valuable adjunct but not a substitute for other urologic diagnostic procedures. Cytology offers particular advantage in the detection of pre-clinical cancer and the primary diagnosis of high grade carcinomas. The procedure is of limited value in the diagnosis of benign papilloma and low grade tumors. However, in such cases diagnostic accuracy could be improved by examining bladder irrigation samples, multiple samples, and basing the diagnosis of the identification of papillary clusters rath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…A review of 17 published series showed that, at worst, the false-negative rates were more than 50% for primary bladder cancer and averaged nearly 75% for superficial low grade disease. 6 An important diagnostic principle is that the higher the grade of the tumour, the more accurate the diagnosis. [7][8][9][10] Despite the limitations, urine cytology remains very useful in the monitoring of patients with high-grade, superficial, urothelial carcinoma where sensitivity and specificity are in the region of 90%.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 17 published series showed that, at worst, the false-negative rates were more than 50% for primary bladder cancer and averaged nearly 75% for superficial low grade disease. 6 An important diagnostic principle is that the higher the grade of the tumour, the more accurate the diagnosis. [7][8][9][10] Despite the limitations, urine cytology remains very useful in the monitoring of patients with high-grade, superficial, urothelial carcinoma where sensitivity and specificity are in the region of 90%.…”
Section: Discussionmentioning
confidence: 99%
“…TPA detection in urine cytology aids in the follow-up of UBC patients, focusing on the actual functional status of the neo plastic urothelial cells [12,30,33] derived from un classified tumors. On the basis of our results, the limitations of conventional urinary cytology [16,20] could be successfully reduced by assaying for TPA in well-differentiated tumors. Samples collected at follow-up, as well as those obtained from high-risk patients for UBC, should be assayed for TPA to ac quire more information concerning the biology and behavior of the tumor for a better management of cancer patients.…”
Section: Discussionmentioning
confidence: 70%
“…Conventional urine cytology is often inadequate for distinguishing between cells derived from benign bladder papillomas [18,22,24,27,28] and those from well-differentiated UBC [16]. In particular, it was ob served that urine cytology was less often positive in first grade PTCT than in second or third grades [29], In these conditions, several routine cytological evalua tions of urinary samples from each patient need to be requested to provide a suitable diagnosis in the man agement and follow-up of UBC patients [24,25],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported sensitivity of urinary cytology ranges from 44.7% to 87.3% with a mean of 73.8%, 9 whereas the X 100. ^j X 100 = 90%.…”
Section: Discussionmentioning
confidence: 99%